ENHANCING STUDENT LEARNING IN PHYSICS BY MOTIVATING THEM - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2018)
ARCS motivation model includes attention, relevance, confidence, and satisfaction. The ARCS model assumes that strategies embedded in instructional materials can enhance the learner's attention to the materials and perceptions of relevance, confidence and satisfaction about learning from them, which in turn enhances cognitive performance. While some studies offered positive effects of ARCS model on learning, some of them did not. More research is needed to discover if implementation of ARCS during instruction improves students' achievement. Therefore, the purpose of this study was to examine the effects of ARCS motivation model on students' learning in physics. Quasi-experimental design by using quantitative research methods was carried out for this study. Participants of the study were 59 10th grade students studying in a public high school. There were 31 students in the experimental group. The research was conducted during six-week instruction of electricity. 5E Instructional Model was implemented in the control and experimental groups. The teacher of both groups was the same. The only difference between the groups was embedding of the ARCS model in to the experimental group's instruction. The results of this study presented that although both groups showed significantly higher performance in the Electricity Concept Inventory in the post-tests than they showed in the pre-tests, the increase in the experimental group was higher than the increase in the control group. It can be concluded from the results that ARCS motivation model affects students' learning in physics positively and improves it. Hence, this study suggests that increasing student motivation should come into prominence in science classes to provide opportunities for students to understand science concepts.
Keywords: ARCS motivation model; learning; physics